Oral Mucositis in Cancer and Potential Use of Omega-3 Free Fatty Acids in Its Management: A Review - Roberta Cardim Lessa (MDPI AG, 2021)
Oral mucositis (OM) is a painful condition caused by chemotherapeutic or radiotherapeutic cancer treatments, occurring in patients with different tumour characteristics and locations. OM greatly impacts a patient’s quality of life and cancer recovery. Current OM management strategies are not providing sufficient prevention and treatment; new approaches to injury management are needed. Studies on the benefit of omega-3 free fatty acids (FFA) in human health have increased significantly in recent years. FFA properties have been studied extensively, including their potential therapeutic use in inflammatory conditions. However, omega-3 FFA’s use as a supplementary treatment for OM has not been clinically tested. Preliminary evidence suggests that utilising FFA to manage OM could be a useful strategy for lesion management, assisting with healthy oral mucosa recovery. This review will describe the incidence, risk factors, biology of OM and the current treatment strategies, leading to a discussion of the utility of omega-3 FFA as a novel therapeutic agent for OM.